Evaluating differential expression of fibrosis-related genes and their correlation with blood vessel density in chronic cutaneous graft-versus-host disease. Issue 1 (July 2022) - Greenberger, Shoshana; Warshavsky, Karin; Goldstein, Gal; Leichner, Gil S.; Tsafrir, Yaron; Manevitz-Mendelson, Eugenia; Baum, Sharon; Barzilai, Aviv
Abstract: Background: Sclerodermoid graft-versus-host disease (GVHD) is the most severe form of chronic GVHD (cGVHD) and represents a considerable therapeutic challenge. Due to the scarcity of human studies on sclerodermoid cGVHD, the pathogenesis of this entity is not fully understood. Objective: To identify the differential expression of fibrosis-related genes in skin lesions of human lichenoid and sclerodermoid cGVHD and to assess the expression of their corresponding proteins. Methods: PCR array analysis was performed on RNA extracted from three skin biopsies of sclerodermoid cGVHD patients and three normal skin samples, for fibrosis-related gene expression profiles followed by evaluation of their corresponding protein expressions. The expressions of Tissue inhibitor of metalloproteinase 3 (TIMP3), matrix metalloproteinase 1 (MMP1), TIMP1, and TIMP2 were further studied by immunohistochemistry. Demographic, clinical and immunohistochemical parameters of the two cGVHD groups and the control group were compared. The Pearson correlation coefficient was used to assess the correlation between data among the study groups. Results: We identified 44 upregulated and 14 downregulated genes in the skin samples of sclerodermoid cGVHD compared to the control group. TIMP3 was positive in 13/21 biopsies of cGVHD and in one biopsy of the control group. The average staining intensity was significantly higher in the cGVHD group compared to the control group. TIMP3 was expressed mainly in dermal blood vessels. cGVHD specimens with positive TIMP3 staining had a statistically significantly higher total microvascular area than the negative specimens. Conclusion: TIMP3 levels are increased in both subtypes of cGVHD and are associated with increased dermal vascularity. Highlights: Gene expression array revealed increase in the expression of matrix metalloproteinases and tissue inhibitor of metalloproteinases in chronic cutaneous GVHD (cGVHD) compared to normal skin controls. By immunostaining we observed increased TIMP3 levels in both lichenoid and sclerodemoid cutaneous cGVHD, mainly in dermal blood vessels.